2022
DOI: 10.2147/rru.s359715
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Platelet Count and Survival in Prostate Cancer

Abstract: Purpose A number of studies have confirmed that elevated platelet count accompanying various solid tumours is associated with worse survival. However, only meagre data are available on the relationship between thrombocytosis and survival in prostate cancer. Methods We conducted a retrospective analysis on clinical-pathological data accumulated from 316 patients during on average 51 months of follow-up after laparoscopic prostatectomy performed for prostate cancer. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Sylman et al reported a significant correlation between increased PLT counts and reduced overall survival in patients with PCa, suggesting that the PLT count could serve as a valuable prognostic indicator for prostate cancer 38 . Nevertheless, in another study, the researchers showed no association between elevated PLT counts and the clinical-pathological characteristics or prognosis of PCa patients, which is consistent with our study findings 39 . The discrepant findings among studies could potentially be attributed to the absence of standardized inclusion and exclusion criteria, differences in the patient populations investigated, as well as variations in the laboratory testing methods and reagents employed.…”
Section: Discussionsupporting
confidence: 92%
“…Sylman et al reported a significant correlation between increased PLT counts and reduced overall survival in patients with PCa, suggesting that the PLT count could serve as a valuable prognostic indicator for prostate cancer 38 . Nevertheless, in another study, the researchers showed no association between elevated PLT counts and the clinical-pathological characteristics or prognosis of PCa patients, which is consistent with our study findings 39 . The discrepant findings among studies could potentially be attributed to the absence of standardized inclusion and exclusion criteria, differences in the patient populations investigated, as well as variations in the laboratory testing methods and reagents employed.…”
Section: Discussionsupporting
confidence: 92%
“…Prostate cancer (PCa) is the most common cancer diagnosed in men accounting alone for 26% of diagnoses in 2021 in the United States, according to population-based cancer incidence data collected by the National Cancer Institute's (NCI's) Surveillance, Epidemiology, and End Results (SEER) program. 1,2 Europe had an all-age incidence ASR of 63 per100000males (473 334 estimated new cases in the year 2020). 3 The role of chronic inflammation in carcinogenesis has been widely studied, and it is estimated that it may contribute to the development of up to 20% of all adult cancers.…”
Section: Introductionmentioning
confidence: 99%